Current knowledge of scoliosis in physiotherapists and physiotherapy students trained in Turkey - KURU ÇOLAK, TUĞBA (My University, 2022)
Purpose: Present evidence suggests that early detection and correct management is an essential part of scoliosis treatment. Therefore, the physiotherapists and physiotherapy students must have adequate knowledge of scoliosis. The purpose of this study was to evaluate the current knowledge of physiotherapists and physiotherapy students in Turkey on scoliosis. Methods: A previously designed questionnaire based on International Society on Scoliosis Orthopaedic and Rehabilitation Treatment (SOSORT) guideline consists of two sections was used in this study. The first section included eight questions to evaluate the knowledge level on the definition, cause, development, prevalence, diagnosis, treatment, and bracing of scoliosis. The second section included three multiple-choice questions to analyze the participants’ opinions on exercises for scoliosis. All Turkish universities offering physiotherapy degrees and graduated physiotherapists from certain social media groups were invited to participate in the study. Results: 649 physiotherapists and 497 students completed the questionnaire. Scoliosis is recognized as a 3-dimensional deformity of the spine by 39.8% of the students and 57.2% of the physiotherapists. Only 19.5% of the students and 30.7% of the physiotherapists correctly identified the diagnostic criteria for scoliosis. For therapeutic exercise, 48.7% of the students and 61.3% percent of the physiotherapists identified the appropriate approach, and also 57.3% of the students and 62.6% of the physiotherapists correctly identified the bracing recommendations. Conclusion: Results of this study showed that physiotherapists and physiotherapy students do not have sufficient knowledge of scoliosis. Action needs to be taken to improve the awareness and basic knowledge level of scoliosis.

Amaç: Güncel kanıtlar, erken teşhis ve doğru yönlendirmenin skolyoz tedavisinin önemli bir parçası olduğunu göstermektedir. Bu nedenle fizyoterapistlerin ve fizyoterapi öğrencilerinin skolyoz konusunda yeterli bilgiye sahip olmaları gerekir. Bu çalışmanın amacı, Türkiye'deki fizyoterapistlerin ve fizyoterapi öğrencilerinin skolyoz hakkındaki güncel bilgilerini değerlendirmektir. Yöntem: Çalışmada Uluslararası Skolyoz Ortopedik Tedavi ve Rehabilitasyon Derneği (Society on Scoliosis Orthopaedic and Rehabilitation Treatment - SOSORT) kılavuzu temel alınarak hazırlanan 2 bölümden oluşan online bir anket kullanılmıştır. İlk bölüm skolyozun tanımı, nedenleri, gelişimi, prevalansı, tanısı ve tedavisi hakkında genel bilgi düzeyini değerlendiren 8 sorudan; ikinci bölüm ise skolyoz için egzersizler hakkındaki görüşleri değerlendiren çoktan seçmeli 3 sorudan oluşmaktadır. Lisans düzeyinde fizyoterapi eğitimi alan öğrenciler ve mezun fizyoterapistler sosyal medya grupları kullanılarak çalışmaya katılmaya davet edilmiştir. Sonuçlar: 649 fizyoterapist ve 497 öğrenci anketi tamamlamıştır. Skolyoz, öğrencilerin %39,8'i ve fizyoterapistlerin %57,2'si tarafından omurganın 3 boyutlu bir deformitesi olarak tanımlanmaktadır. Öğrencilerin sadece %19,5'i ve fizyoterapistlerin sadece %30,7'si skolyoz için tanı kriterlerini doğru bir şekilde tanımlamıştır. Terapötik egzersiz için öğrencilerin %48,7'si ve fizyoterapistlerin %61,3'ü uygun yaklaşımları tanımlamıştır ve öğrencilerin %57,3'ü ve fizyoterapistlerin %62,6'sı korse kullanımı önerilerini doğru bir şekilde tanımlamıştır. Tartışma: Bu çalışmanın sonuçları fizyoterapistlerin ve fizyoterapi öğrencilerinin skolyoz hakkında yeterli bilgi düzeyine sahip olmadığını ortaya koymuştur. Skolyoz farkındalığını ve temel bilgi düzeyini arttırmak için harekete geçilmesi gerekmektedir.
Türkiye’de eğitim gören fizyoterapi öğrencilerinde ve fizyoterapistlerde güncel skolyoz bilgisi
Keywords: Education; Knowledge; Physical Therapist; Scoliosis; Turkey; University; Eğitim; Bilgi; Fizyoterapist; Skolyoz; Türkiye; Üniversite